Uniparental disomy of chromosome 21: A statistical approach and application in paternity tests. (November 2020) - Cavalheiro, C.P; Avila, E.; Gastaldo, A.Z.; Graebin, P.; Motta, C.H.A.; Rodenbusch, R.; Alho, C.S.
Highlights: 350 markers were tested by capillary electrophoresis and massive parallel sequencing. Statistical approach for Uniparental Disomy in a trio paternity case. Uniparental Disomy seems to explain with greater probability the genetic inconsistences between alleged father and child. A significant number of UDP cases probably remain undetected in regular paternity trios tests. Abstract: Considering the overall frequency of paternity investigation cases including mutational events, there is a real possibility that at least a fraction of all inconsistencies reported in paternity cases are caused not by polymerase slippage mutations, but to chromosomic abnormalities, as Uniparental Disomy (UPD). We report here the investigation of a trio paternity case (mother, child and alleged father), with observed inconsistencies that can alternatively be explained by occurrence of maternal uniparental isodisomy of chromosome 21 (miUPD21). A total of 350 short tandem repeat (STR) and single nucleotide polymorphism (SNP) markers were tested, statistically suggesting true biological linkage within the trio. Additionally, we propose miUPD21 explains, with significantly greater probability, the occurrence of detected inconsistencies, when compared to alternative hypothesis of multiple and simultaneous slippage mutations. Similar cases could have their statistical conclusions improved or even altered by including unusual chromosomal segregation patterns in the hypothesis formulation, as well as in mathematical calculations. Such reports of allelic inconsistencies being explained by chromosomal alterations are common in clinical genetics, and such situations might have impact on forensic investigation.